Concrete in coastal structures - Allen, R. T. L. (Thomas Telford, 1998)
This reference text covers all aspects of the design construction, maintenance and repair of concrete coastal structures.
Keywords: Coastal engineering.; Shore protection.; elektronické knihy; electronic books